2015
DOI: 10.1519/jsc.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on Anthropometrical, Physical Fitness, and Motor Coordination Characteristics That Influence Dropout, Contract Status, and First-Team Playing Time in High-Level Soccer Players Aged Eight to Eighteen Years

Abstract: The goal of this article was twofold, and a 2-study approach was conducted. The first study aimed to expose the anthropometrical, physical performance, and motor coordination characteristics that influence dropout from a high-level soccer training program in players aged 8-16 years. The mixed-longitudinal sample included 388 Belgian youth soccer players who were assigned to either a "club group" or a "dropout group." In the second study, cross-sectional data of anthropometry, physical performance, and motor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
153
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(175 citation statements)
references
References 36 publications
15
153
3
4
Order By: Relevance
“…Depending on the coaches understanding on when it is to late to become an professional football player, these players should be given the opportunity to develop within their team, to maximize their potential. Furthermore, the players' ability to develop coping strategies (Reeves et al, 2009) could also be important, especially because the research indicates the difficulty of identifying potentially top-level players at an early age (Deprez, Fransen, Lenoir, Philippaerts, & Vaeyens, 2015;Saether, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the coaches understanding on when it is to late to become an professional football player, these players should be given the opportunity to develop within their team, to maximize their potential. Furthermore, the players' ability to develop coping strategies (Reeves et al, 2009) could also be important, especially because the research indicates the difficulty of identifying potentially top-level players at an early age (Deprez, Fransen, Lenoir, Philippaerts, & Vaeyens, 2015;Saether, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, physical fitness in sport has a more specific definition, and its correlation with performance has been investigated in previous studies [2,9,13,23,24,27]. In this sense, some components needed to practice field hockey at a high level of performance are: agility to perform quick changes of direction without loss of speed, efficiency to recover between sprints, endurance of the stabilizing muscles of the spine to maintain the adopted posture during practice, and technical skills [18].…”
Section: Introductionmentioning
confidence: 99%
“…Correlations between these variables and sports performance are widely related in the scientific literature in several sports [9,14,15,29,30,34].…”
Section: Introductionmentioning
confidence: 99%
“…He also reiterated that the development of anaerobic power occurs when submitted to systematic training and specialized sports, which makes it extremely important for the evaluation and follow-up of the athlete to obtain the rates of bone maturation, as a determining factor of the sports performance that will influence In the planning of the training load for better accuracy in the individualization, mainly in terms of methods and intensity. Following this line of reasoning, this study recommended the statistical comparison with the anaerobic power variable obtained by the MY JUMP vertical jump test, validated in the Balsalobre-Fernández study [8] , which showed a peak of out-ofcurve performance for the U-13 category, and came to contradict reference data from a large retrospective study by Deprez et al [25] that found statistical evolution of the performance of the physiological variable and anaerobic power only from the age of 16 years old on; That, above this age group, the results obtained here are aligned with the exponential development progression in this maturational period, which reflects the reach of the final stages, maintaining a better constancy of results and responsiveness to the training intervention.…”
Section: Discussionmentioning
confidence: 99%